PEMBENTUKAN AKHLAK RENDAH HATI (TAWADHU') DALAM CERAMAH UST HANAN ATTAKI DI YOUTUBE - Siti Aisyah; Fito Amirul Pradonansyah; Marta Rico Saputra; M. Rifqi Al-Aziz; Ibnu Rozali (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
The formation of noble character in the younger generation is a central issue in contemporary Islamic education. Religious lectures through digital media, especially YouTube, have become one of the most effective da'wah mediums to reach teenagers and millennial generations. Ustadz Hanan Attaki is known as a preacher who is able to package Islamic moral messages, including the value of tawadhu' (humility), in language that is relevant and easy to understand by young people. This article aims to analyze how tawadhu' values are conveyed and formed through Ustadz Hanan Attaki's lectures on YouTube, as well as their relevance in shaping the character of young Indonesian Muslims. The research method uses a descriptive qualitative approach with content analysis technique on lectures uploaded on Hanan Attaki's official YouTube channel. The results show that Ustadz Hanan Attaki's lectures consistently contain tawadhu' messages packaged in contemporary narratives, including anti-showing-off attitudes, respecting others, accepting advice, and prioritizing others' interests. The communicative da'wah strategy that is close to the reality of young people's lives makes these lectures effective in instilling tawadhu' values as part of Islamic character formation.